2020
DOI: 10.5296/jas.v8i4.17314
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thyme and Tansy Extracts Used as Basic Substances in Zucchini Crop Protection

Abstract: Bio-sourced substances used for crop protection in natural and organic farming have a positive impact both on human and environment health: plant extracts are effective to stimulate plant defense against pests and diseases, with no toxic effect and they could be classified as basic substances. The chemical characterization of thyme and tansy extracts were carried out with ICP and NMR techniques for the analysis of elemental content and organic components. Antioxidant activity was evaluated by DPPH method. Phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The biological properties of aromatic plants and medicinal plants rich in essential oils include biostimulant properties [47]. In particular, rosemary [47,48], eucalyptus [48], thyme [49,50] and tansy [50] are the most popular herbs. Among the essential oils extracted from rosemary and eucalyptus are 1,8-cineole, which has antibacterial, antifungal, herbicidal, and insecticidal properties [48].…”
Section: Resultsmentioning
confidence: 99%
“…The biological properties of aromatic plants and medicinal plants rich in essential oils include biostimulant properties [47]. In particular, rosemary [47,48], eucalyptus [48], thyme [49,50] and tansy [50] are the most popular herbs. Among the essential oils extracted from rosemary and eucalyptus are 1,8-cineole, which has antibacterial, antifungal, herbicidal, and insecticidal properties [48].…”
Section: Resultsmentioning
confidence: 99%
“…Aromatic plants and medicinal plants rich in essential oils are known to have a wide range of biological activities including biostimulant properties (Souri and Bakhtiarizade, 2019). Among them, the most popular are rosemary (Souri and Bakhtiarizade, 2019;Chrysargyris et al, 2020), eucalyptus (Chrysargyris et al, 2020), thyme (Ben-Jabeur et al, 2019;Beni et al, 2020), tansy (Beni et al, 2020). Essential oils extracted from rosemary or eucalyptus contain 1,8-cineole, which is known to possess antibacterial, antifungal, herbicidal, and insecticidal properties (Chrysargyris et al, 2020).…”
Section: Effect Of Plant-based Biostimulants On Plant Growth Development and Qualitymentioning
confidence: 99%
“…Essential oils contain a mixture of compounds, specific for each plant, which includes, among others: aldehydes, alkaloids, carotenoids, flavonoids, isoflavones, monoterpenes, phenolic acids, and oxygen-containing, and non-oxygenated terpene hydrocarbons (Zanellato et al, 2009;Fierascu et al, 2020;Ni et al, 2021). Essential oils extracted from aromatic plants can be used not only as sprays, fumigants, or granular formulations but also for seeds coating (Benvenuti et al, 2017;Beni et al, 2020). Ben-Jabeur et al (2019) showed that seed treatment with thyme oils can improve the plant's water and nutrient status and can enhance drought resistance.…”
Section: Effect Of Plant-based Biostimulants On Plant Growth Development and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, thyme extract was shown to be utilized for crop protection of zucchini an alternative to chemical pesticides. The field trials revealed that thyme extract could be used as phyto-stimulant and plant strengthening hence increased crop yield [8].…”
Section: Introductionmentioning
confidence: 99%